Quorum Sensing Inhibition and Metabolic Intervention of 4-Hydroxycinnamic Acid Against Agrobacterium tumefaciens - Zhou, Jin-Wei; Ji, Peng-Cheng; Jiang, Huan; Tan, Xiao-Juan; Jia, Ai-Qun (Frontiers in Microbiology, 2022)
The natural product 4-hydroxycinnamic acid (HA) was firstly isolated from the metabolites of Phomopsis liquidambari, one endophytic fungus from Punica granatum leaves. The anti-QS potential of HA was evaluated by β-galactosidase assay and acylated homoserine lactones (AHL) analysis. The MIC of HA was > 1.20 mM. Exposure to HA at sub-MIC concentrations (0.30-0.60 mM) remarkably reduced the β-galactosidase activity and AHL secretion. Transcriptional analysis by qRT-PCR and docking simulation indicated that HA functions as an anti-QS agent by inhibiting the transcriptional levels of traI and traR rather than signal mimicry. The blocked QS lead to suppressed biofilm formation, motilities, and flagella formation after exposure to HA at concentrations ranging from 0.30 to 0.80 mM. The dysfunctional QS also resulted in repressed antioxidant enzymes and intensified oxidative stress. The intensified oxidative stress destroyed membrane integrity, induced energy supply deficiency, resulted in disorder of protein and nuclear acid metabolism, and ultimately weakened pathogenicity of A. tumefaciens. HA may have promising potential for controlling A. tumefaciens.